A Counsellor's Assessment of Love Development in Mate Selection and Marriage - Adams, Wesley J. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article offers a typology for viewing love as the development of an interpersonal relationship in five stages. As a typology the author believes it has implications for both counselling and teaching purposes. In teaching, both clarity and precision can be gained by explicit conceptualization of love, while in counselling greater understanding and awareness may be generated through mutual discussion with couples who are in various stages in their love development. Such development may be viewed during mate selection or marriage in its many stages.